The effects of IPA II pre-accession assistance instruments in Bosnia and Herzegovina, Kosovo, and Turkey - Suada A. Džogović; Anita Cucović; Suada Ajdarpašić; Enes Hamzagić (Management : Journal of Contemporary Management Issues, 2021)
Provided that one of the goals of the European Union (EU) is the economic development and possibility of integration by implementing fundamental reforms through an adequate strategic approach, this paper aims to determine the impact of the EU policy and the Instrument for PreAccession Assistance (IPA Fund) on the international business environment with special emphasis on Bosnia and Herzegovina, Kosovo, and Turkey. It is obvious that the EU not only provides assistance to candidate countries but also contributes to the stability, security, and prosperity of beneficiary countries. However, by adopting this approach, the EU imposes certain changes in the instruments of financial support. Namely, by launching the IPA II programme it surpassed IPA I, covering five priority areas as the key segments of development. It has been shown that this support programme is of great importance for the development of the countries covered in this study. Our research also indicates that IPA funding aids in the political and economic reforms of transition countries, preparing them for the rights and duties that come with the Union membership. Secondary data available on the official website of the European Union were used in this study. The hypothesis is confirmed by quantitative data analysis showing a significant impact of the IPA II programme on defined sectors in Bosnia and Herzegovina, Kosovo, and Turkey.